Relações entre autenticidade e motivação no desenvolvimento da produção escrita por jovens aprendizes de língua estrangeira (inglês), a partir do gênero notícias de jornal - Guedes, Roberta de Oliveira (2011)
When studying the literature in the area of teaching and learning languages, two multifaceted and meaningful concepts can be identified, they are authenticity (GILMORE, 2007) and motivation (DÖRNYEI, 2001; VIANA, 1990). Concerning the integration of both themes, Gilmore (2007) points out that, although there is common belief about the motivating potential of authentic materials, there is little empirical support for stating the existence of this relationship. This research investigates which relations may be established between authenticity and motivation through the development of activities that focus on the genre newspaper report in the English language classrooms for learners who participate in an extension program at a Federal University in Sao Paulo State. The choice of this genre as a combination of both theories was made based on its relevance in the New Curriculum Proposals for the State of São Paulo and also due to the lack of studies that guide the pedagogical practice in the development of meaningful activities through genre. (OLIVEIRA, 2010). Therefore, based on the data analysis and the conclusion of this study, it is possible to verify how through the genre newspaper reports it is possible to integrate authenticity and motivation, reflecting on students-participants‘ behavior, their written productions and in the teaching and learning of languages.